Molecular Diagnosis of oyster mushroom Pleurotus ostreatus and screening for resistance gene of plant pathogenic fungi Osterolysin - Samir Abdul Amir Saadoun; Sulaf Hamid Timosz (Al-Qadisiyah Journal of Pure Science, 2018)
The experiment in the laboratory of research in the College of Veterinary Medicine /AL- Qadisiya University of identify the innate agricultural White (mushroom oyster Pleurotus ostreatus) in terms of molecular using the technique of the interaction of the chain monomer PCR, which was obtained Sporadtha from different places, it has included the results of multiplying the vaccine is innate to the center of the PDA it then took him filaments were grown on the center of the brain and brain infusion BHI so as to facilitate access to the DNA. The results showed that as the oyster mushrooms grow well on the center of the potato dextrose Acar during the period 4-7 days at a temperature of 30 MÛ• and prolong the period when cuddling to 10 days for the appearance of buds was observed as the beginning of fruiting bodies. Then move disks from spinning mildew fungus shellfish to the center of infusion brain and the brain fluid of 15 samples for the purpose of preparing for the diagnosis. Observed through the application of the technique polymerization and doubling of DNA and then note the quantity of samples in Nanodrop contain all the samples contain all isolates on a single package and single of DNA extracted was the results were positive for all the samples left on the gel Alakaros but there is a lack of clarity of some of the samples, but the packages of DNA were present in the samples that were not clear exaggerated enough, either in the case of amplification of genes mushrooms to investigate the gene responsible for resistance mushroom oyster-fungal plant pathogens the volume of output of nucleic acid amplification multiplier with bp 303 and all samples contain a gene responsible for a recipe Osterolysin resistance in the oyster mushrooms.